THE MEASUREMENT OF LOCAL PLASTIC-DEFORMATION IN A METAL-MATRIX COMPOSITE BY ELECTRON BACKSCATTER PATTERNS - Wilkinson, A; Gonzalez, G; Dingley, D (1993)
High dislocation densities in the matrices of metal-matrix composites (MMCs) contribute to the strengthening of particulate MMCs, whilst heterogeneous nucleation of precipitates at these defects can cause marked differences in the age hardening of many matrix alloys. Electron backscatter patterns (EBSPs) and transmission electron microscopy (TEM) have been used to examine the dislocation distribution in continuous-fibre SiC/Al alloy MMCs. TEM observations showed dislocation densities as high as 3 x 1014 m-2, with a marked increase as thinner matrix regions were observed. From EBSP measurements on bulk specimens, a much lower dislocation density of 2 x 1012 m-2 was estimated. To resolve this discrepancy, EBSP measurements were made from thinned TEM specimens and these showed that the dislocation density had increased during specimen thinning. However, both TEM and EBSP measurements from unreinforced matrix material prepared for TEM using the same procedures showed no such increase in dislocation density. Redistribution of internal stresses during thinning of the composite to a transparent foil must therefore be the cause of the observed rise in dislocation density. The EBSP technique was demonstrated to be an excellent means of examining the distribution of plastic deformation in MMCs. It was concluded that TEM measurements of dislocation densities in continuous-fibre MMCs can be erroneously high.